Embedded self-conceptualization and social learning in online social networking platforms - Yu, Yan (Frontiers in Psychology, 2022)
Online social networking (OSN) has deeply penetrated university campuses, influencing multiple aspects of student life. Standing from a pedagogical perspective, this study investigates how university students’ OSN engagement affect their learning outcomes. Drawn upon social learning theory, this study proposes that OSN engagement help university students’ establishing the self-efficacy belief, achieving social acceptance and acculturation with environment, and these attributions further lead them to attain positive learning outcomes which are shaped by self-esteem development, satisfaction with university life, and the grade point average (GPA) based performance. Results from a survey accompanied by focus group discussions support these embedded self-conceptualization and social learning in OSN. This study contributes to the extant research on OSN for learning by highlighting the role of OSN for the whole person development, especially the students’ self-conceptulization and psychological well-beings. The revealed mediating mechanisms also adds values to social learning theory and imply the design foci of e-learning activities and applications.